Pseudomonas aeruginosa biofilms perturb wound resolution and antibiotic tolerance in diabetic mice - Watters, Chase (2012)
Diabetic patients are more susceptible to the development of chronic wounds than non-diabetics. The impaired healing properties of these wounds, which often develop debilitating bacterial infections, significantly increase the rate of lower extremity amputation in diabetic patients. We hypothesize that bacterial biofilms, or sessile communities of bacteria that reside in a complex matrix of exopolymeric material, contribute to the severity of diabetic wounds. To test this hypothesis, we developed an in vivo chronic wound, diabetic mouse model to determine the ability of the opportunistic pathogen, Pseudomonas aeruginosa, to cause biofilm-associated infections. Utilizing this model, we observed that diabetic mice with P. aeruginosa-infected chronic wounds displayed impaired bacterial clearing and wound closure in comparison with their non-diabetic littermates. While treating diabetic mice with insulin improved their overall health, it did not restore their ability to resolve P. aeruginosa wound infections or speed healing. In fact, the prevalence of biofilms and the tolerance of P. aeruginosa to gentamicin treatment increased when diabetic mice were treated with insulin. Insulin treatment was observed to directly affect the ability of P. aeruginosa to form biofilms in vitro. These data demonstrate that the chronically wounded diabetic mouse appears to be a useful model to study wound healing and biofilm infection dynamics, and suggest that the diabetic wound environment may promote the formation of biofilms. Further, this model provides for the elucidation of mechanistic factors, such as the ability of insulin to influence antimicrobial effectiveness, which may be relevant to the formation of biofilms in diabetic wounds.